Retinofugal Projections Into Visual Brain Structures in the Bat Artibeus planirostris: A CTb Study - Santana, Melquisedec A. D.; Medeiros, Helder H. A.; Leite, Mariana D.; Barros, Marília A. S.; de Góis Morais, Paulo Leonardo Araújo; Soares, Joacil Germano; Ladd, Fernando V. L.; Cavalcante, Jeferson S.; Cavalcante, Judney C.; Costa, Miriam S. M. O.; Nascimento Jr., Expedito Silva (Frontiers in Neuroanatomy, 2018)
A well-developed visual system can provide significant sensory information to guide motor behavior, especially in fruit-eating bats, which usually use echolocation to navigate at high speed through cluttered environments during foraging. Relatively few studies have been performed to elucidate the organization of the visual system in bats. The present work provides an extensive morphological description of the retinal projections in the subcortical visual nuclei in the flat-faced fruit-eating bat (Artibeus planirostris) using anterograde transport of the eye-injected cholera toxin B subunit (CTb), followed by morphometrical and stereological analyses. Regarding the cytoarchitecture, the dorsal lateral geniculate nucleus (dLGN) was homogeneous, with no evident lamination. However, the retinal projection contained two layers that had significantly different marking intensities and a massive contralateral input. The superior colliculus (SC) was identified as a laminar structure composed of seven layers, and the retinal input was only observed on the contralateral side, targeting two most superficial layers. The medial pretectal nucleus (MPT), olivary pretectal nucleus (OPT), anterior pretectal nucleus (APT), posterior pretectal nucleus (PPT) and nucleus of the optic tract (NOT) were comprised the pretectal nuclear complex (PNT). Only the APT lacked a retinal input, which was predominantly contralateral in all other nuclei. Our results showed the morphometrical and stereological features of a bat species for the first time.